SIKAP DA’I TERHADAP MUKTAZILAH DAN SYIAH DALAM PENGEMBANGAN DAKWAH DAMAI (Studi Analisis Surat Ali Imran Ayat 105 dan An-Nisa` Ayat 59) - Azizi, Muhammad Abrar; Aminullah, Muhammad (KOMUNIKE, 2021)
Living in a pluralistic or global society, the difference in understanding becomes a challenge in the concept of society. Differences need to be addressed carefully, so as not to cause conflict and enmity between groups in society. A dai must have a professional attitude in dealing with a pluralistic society. Therefore, it is necessary to re-examine the verses of the Al-Qur`an which explain the attitude of dai in dealing with different thoughts. This research uses Thematic Tafsir method, with the approach to the interpretation of the verses of the Al-Qur`an. The verses used in this study are interpreting Surah Ali Imran verse 105 and An-Nisa` verse 59. The results of the research found that someone who dai must have a professional attitude in dealing with differences. Differences in thought must be addressed wisely, namely differences are allowed but do not cross the line. Differences that can no longer be understood, do not impose justification on yourself, surrender the truth with confidence to Allah and the Messenger.